Pengaruh Bridge Simulator Karya PT. LEN Sebagai Industri Pertahanan Dalam Negeri untuk Meningkatkan Kompetensi Taruna AAL Korps Pelaut - Rahmat Alkadri; Basri Mustari; Agung Setiawan (Rekayasa, 2022)
The Indonesian Navy is a military force owned by the State of Indonesia. One of the main components of the Indonesian Navy is a warship (KRI). The role of the KRI in the implementation of the peak training of the jaya fleet is to carry out various ship formations which will later be used during operations. This study was conducted to describe the increase in the learning outcomes of Marine Corps AAL cadets on the use of the Bridge Simulator. The type of research used is Pre-experimental with One Group Pretest and Posttest Design. The research subjects were AAL cadets Level III and Level IV Marine Corps. The results of this study indicate the learning outcomes of cadets. Paired t-test data analysis using SPSS 25 for windows showed sig (2 tailed) 0.00 less than 0.05, which means H0 is rejected so that there is a significant increase in learning outcomes. The use of the Bridge Simulator can improve the learning outcomes of Marine Corps AAL cadets.